A method for molten metal-induced construction of strong metal-support interaction in metal catalysts
SMSI was constructed on a supported metal catalyst by molten metal induction, which solved the problem of unstable SMSI in the high-temperature oxidation atmosphere in the prior art, and expanded its application range to multi-metal systems, achieving high stability and activity of the catalyst.
Patent Information
- Application Number
- CN202310568937.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-05-16
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2043-05-16
AI Technical Summary
The prior art is difficult to stabilize the metal-carrier strong interaction (SMSI) in high-temperature oxidation atmospheres, and the application of SMSI in binary or multivariate metal systems is very limited.
Through the molten metal induction method, the metal powder of the supported metal catalyst is covered and processed in a high-temperature argon atmosphere to form a stable oxide coating layer to achieve SMSI construction and alloying at the same time.
The stability of SMSI in high-temperature oxidation atmosphere is achieved, the application range of SMSI is expanded to complex reaction environments and multi-metal systems, and the stability and activity of the catalyst are improved.
Smart Images

Figure CN116532127B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of multiphase catalyst preparation, and in particular relates to a method for inducing strong metal-carrier interaction in a metal catalyst by molten metal. Background Art
[0002] The information disclosed in this background technology section is only intended to enhance the understanding of the overall background of the invention, and should not necessarily be regarded as an admission or any form of suggestion that the information constitutes the prior art already known to a person skilled in the art.
[0003] Supported metal catalytic materials are an extremely important type of catalyst in the field of heterogeneous catalysis and are widely used in synthetic chemical industry, energy conversion, pollution treatment, signal detection and other fields. In this type of material, the interaction between the support and the metal can significantly affect the geometric structure and electronic structure of the metal active phase, thus providing a new dimension for the regulation of metal catalyst performance and greatly expanding the possibility of optimizing catalyst selectivity, activity and stability. Therefore, how to understand and utilize the interaction between metal and support is an important research topic in the field of heterogeneous catalysis.
[0004] Strong Metal-Support Interaction (SMSI) is a special interaction that mainly exists between metals and reducible oxide supports. Different from the general interaction between metals and supports, SMSI has the following main characteristics: 1) It is formed under a high-temperature reducing atmosphere; 2) The metal active phase is covered by an amorphous oxide coating layer; 3) The metal active center loses its adsorption capacity for small gas molecules (CO, H2, etc.); 4) The coating fades and disappears under a high-temperature oxidizing atmosphere, and the metal active site recovers its adsorption capacity for small gas molecules, which is reversible. SMSI can not only significantly stabilize the structure of the metal active phase and improve the stability of the catalyst in harsh reaction environments such as high temperature, but also regulate the activity and selectivity of the catalyst through interfacial bonding or electronic interactions. Therefore, it has extremely important applications in industrial reactions such as selective hydrogenation, water vapor conversion, and methanol steam reforming.
[0005] However, in actual applications, this coating produced by the traditional high-temperature H2 reduction method is difficult to be stable in a high-temperature oxidizing atmosphere (such as O2), and will fade, resulting in the disappearance of SMSI, which greatly limits the application of this type of catalyst in an oxidizing environment. In addition, the construction of SMSI is still limited to a single metal system, and reports on the effective construction of SMSI in binary or multi-metal systems are very rare. This may be because alloys and intermetallic compounds have smaller surface energy than single metals, and the surface energy difference between them and the oxide support activated by the traditional high-temperature H2 reduction method will no longer be significant, thereby inhibiting the migration of the support and the formation of the subsequent coating layer. This makes SMSI unable to be used as an effective means to improve the stability of alloy or intermetallic compound-based catalysts in harsh reaction environments. Summary of the invention
[0006] In order to overcome the deficiencies of the prior art, the purpose of the present invention is to provide a method for molten metal-induced construction of a strong metal-support interaction in a metal catalyst. The SMSI constructed by the present invention can be stable in a high-temperature oxidizing atmosphere, and alloying can be achieved while the SMSI is constructed.
[0007] In order to achieve the above object, the technical solution of the present invention is:
[0008] In a first aspect of the present invention, there is provided a method for molten metal-induced construction of a strong metal-support interaction in a supported metal catalyst, comprising the following steps:
[0009] (1) Synthesizing supported metal catalysts by an impregnation method, which include oxide supports and metal nanoparticles, clusters or single atoms;
[0010] (2) After the supported metal catalyst is fully covered with metal powder, the temperature is raised above the melting point of the metal powder under the protection of an inert atmosphere to melt the metal powder, and the temperature is kept for 1-24 hours; after cooling to room temperature, the mixed solid is pickled with concentrated acid, centrifuged, and dried to obtain a supported metal catalyst after the molten metal induces the construction of a strong metal-carrier interaction.
[0011] The above method of the present invention realizes low-cost, large-scale construction of SMSI of supported metal catalysts, provides a new means of molten metal liquid phase reduction, and constructs SMSI in a metal catalyst system with simple process and low cost. After SMSI is constructed, the coating layer of the supported metal catalyst can stably exist in a high-temperature oxidation environment, effectively avoiding the reversibility of SMSI and improving its application potential in an oxidation reaction environment.
[0012] In some embodiments of the present invention, the impregnation method comprises the following steps:
[0013] The oxide carrier is dispersed in water or ethanol and ultrasonically treated to make it uniformly dispersed; then, a metal precursor solution is added dropwise under magnetic stirring, and the solution is stirred dry by heating in a water bath; after the obtained powder is fully ground, a supported metal catalyst is obtained by heat treatment in an atmosphere.
[0014] The concentration of the metal precursor solution is 0.01-10 mol / L, and the temperature of the water bath heating is 40-90°C.
[0015] In some embodiments of the present invention, the mass percentage of metal nanoparticles, clusters or single atoms in the supported metal catalyst is 0.01-60 wt %.
[0016] In some embodiments of the present invention, the oxide carrier is composed of one of TiO2, V2O3, MnO2, Fe3O4, CeO2, Nb2O5, Ta2O5, MgO, Al2O3, SiO2, ZnO or a solid solution thereof.
[0017] In some embodiments of the present invention, the metal nanoparticles are composed of one or more (alloys, intermetallic compounds, etc.) of Fe, Co, Ni, Ru, Rh, Pd, Os, Ir, Pt, Cu, Ag, and Au.
[0018] In some embodiments of the present invention, the metal powder is one or more (alloys, intermetallic compounds, etc.) of Li, Na, K, Mg, Ca, Zn, Cd, Al, Ga, In, Sn, Pb, Sb, and Bi.
[0019] The SMSI of the present invention is constructed by treating a metal catalyst supported on an oxide carrier with a molten metal. In the process of constructing the SMSI, alloying can be simultaneously achieved to form an alloy or an intermetallic compound, thereby expanding the SMSI to metal systems other than Group VIII and Group IB, and improving the stability of alloy and intermetallic compound-based catalysts in harsh reaction environments.
[0020] The second aspect of the present invention provides a supported metal catalyst after molten metal induced construction of strong metal-carrier interaction, which is prepared by the above method. The supported metal catalyst of the present invention is a new material structure and has the potential to be applied in different reaction environments.
[0021] The third aspect of the present invention provides an application of the supported metal catalyst after the molten metal induces the construction of a strong metal-support interaction, wherein the application is used as a catalyst under high-temperature oxidizing atmosphere conditions. The oxide coating layer formed in the molten metal of the present invention is stable in a high-temperature oxidizing atmosphere, and can therefore be applied to complex reaction environments.
[0022] The beneficial effects of the present invention are:
[0023] The invention realizes the construction of SMSI in an oxide-supported metal-based catalyst system at low cost and simple process, and can realize the construction of SMSI of single metal nanoparticles and the construction of SMSI of alloys or intermetallic compounds at different temperatures above the melting point of the metal. The catalyst prepared by the invention is a new type of material structure and has the potential to be applied in different reaction environments.
[0024] The coating constructed by the molten metal can effectively improve the stability of the metal catalyst in a high-temperature environment, avoid the agglomeration and growth of the metal active phase, and thus extend the service life of the catalyst. Secondly, the oxide coating formed in the molten metal can be stable in a high-temperature oxidizing atmosphere, so it can be used in complex reaction environments. In addition, by increasing the processing temperature, the metal active phase can form an intermetallic compound with the molten metal in situ, and finally construct SMSI on the intermetallic compound, which can significantly improve the stability of the intermetallic compound system in harsh environments.
[0025] In summary, the present invention has the advantages of rapid reaction and simple process, realizes the controllable construction of SMSI on metal catalysts, and the coating layer has excellent stability in high-temperature oxidative environment, which can expand SMSI to complex reaction systems and material systems. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] The accompanying drawings in the specification, which constitute a part of the present invention, are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute improper limitations on the present invention.
[0027] Figure 1 TEM spectrum of the titanium dioxide-supported platinum nanoparticle catalyst after SMSI was induced by molten metal tin in Example 1;
[0028] Figure 2 The CO-DRIFTS spectrum of the titanium dioxide-supported platinum nanoparticle catalyst after SMSI was induced by molten metal tin in Example 1;
[0029] Figure 3 This is the EDS surface scan spectrum of the titanium dioxide-supported platinum nanoparticle catalyst after SMSI was constructed by molten metal tin in Example 1;
[0030] Figure 4 The EXAFS wavelet transform spectrum of the titanium dioxide-supported platinum nanoparticle catalyst after SMSI was induced by molten metal tin in Example 1;
[0031] Figure 5 TEM spectrum of the titanium dioxide-supported platinum nanoparticle catalyst after SMSI was induced by molten metal tin in Example 1;
[0032] Figure 6 It is the TEM spectrum in comparative example 1;
[0033] Figure 7 It is the TEM spectrum in Example 2;
[0034] Figure 8 It is the EDS surface scan spectrum in Example 2;
[0035] Fig. 9 This is the EXAFS wavelet transform spectrum in Example 2. DETAILED DESCRIPTION
[0036] In order to enable those skilled in the art to more clearly understand the technical solution of the present invention, the technical solution of the present invention will be described in detail below in conjunction with specific embodiments.
[0037] Example 1
[0038] A method for constructing SMSI on a titanium dioxide-supported platinum nanoparticle catalyst induced by molten metal tin, the specific steps are as follows:
[0039] (1) Preparation method of titanium dioxide supported platinum nanoparticle catalyst:
[0040] First, 40 mg of titanium dioxide was dispersed in 20 mL of deionized water and ultrasonically dispersed. Then, 40 uL of 0.1 mol / L tetraammine nitrate platinum aqueous solution was gradually added under magnetic stirring, and the solution was then stirred dry in a 60°C water bath. After the obtained powder was fully ground, it was placed in a muffle furnace and heated to 200°C at a heating rate of 10°C / min. It was first calcined in air for 5 hours, cooled to room temperature, and then placed in a tubular furnace in an argon atmosphere and calcined at 700°C for 1 hour. The titanium dioxide-supported platinum nanoparticle catalyst was obtained by cooling to room temperature.
[0041] (2) Method of constructing SMSI by inducing molten metal tin:
[0042] After 20 mg of the titanium dioxide-supported platinum nanoparticle catalyst obtained in step (1) was fully covered with 1 g of tin powder, the temperature was raised to 400° C. at a rate of 10° C. / min and calcined for 1 h in a tube furnace under argon atmosphere. After cooling to room temperature, the mixed solid obtained after calcination was dissolved with excess concentrated hydrochloric acid, then centrifuged and washed with deionized water 3 times. Finally, the sample was dried overnight in a vacuum oven at 60° C. to obtain a sample after SMSI was induced by molten metal tin.
[0043] (3) In this example, the titanium dioxide-supported platinum nanoparticle catalyst obtained after molten metal tin induced SMSI was characterized by transmission electron microscopy (TEM), diffuse reflectance infrared spectroscopy of CO adsorption (CO-DRIFTS), energy dispersive X-ray spectroscopy (EDS) and extended X-ray absorption fine structure spectroscopy (EXAFS).
[0044] like Figure 1 As shown, an amorphous coating layer obviously appeared on the surface of platinum nanoparticles supported by titanium dioxide, and the average size of the platinum nanoparticles was about 10 nm.
[0045] like Figure 2 As shown, the sample treated with molten metal tin does not have the characteristic peak of Pt adsorbing CO, that is, the catalyst loses its ability to adsorb CO and a strong metal-support interaction occurs.
[0046] like Figure 3 As shown, signals of titanium, oxygen, and tin appeared at the particles, among which the titanium and oxygen signals came from the outer coating layer.
[0047] Figure 4 The EXAFS wavelet transform results show that the coordination environment of platinum atoms is still the same as that of platinum nanoparticles. Therefore, the tin signal can be judged to also come from the coating layer.
[0048] like Figure 5 As shown, after the catalyst after SMSI was induced by molten metal tin was treated in a pure oxygen environment at 500°C for 1 hour, the coating layer existed stably.
[0049] Comparative Example 1
[0050] SMSI was constructed on a titanium dioxide-supported platinum nanoparticle catalyst using high-temperature hydrogen reduction at 400 °C.
[0051] like Figure 6 As shown, after the catalyst after high-temperature hydrogen reduction-induced SMSI construction was treated in a pure oxygen environment at 400°C for 1 hour, the coating layer could not exist stably and had faded and disappeared.
[0052] Example 2
[0053] A method for constructing SMSI on a titanium dioxide-supported platinum nanoparticle catalyst induced by molten metal zinc: This embodiment is basically the same as the method in Example 1, except that the metal inducing the construction of SMSI is zinc.
[0054] (1) The preparation method of the titanium dioxide supported platinum nanoparticle catalyst is the same as that in Example 1.
[0055] (2) Method of constructing SMSI by inducing molten metal zinc:
[0056] After 20 mg of titanium dioxide-supported platinum nanoparticle catalyst was fully covered with 1 g of zinc powder, it was calcined at 700 °C for 1 h in a tube furnace under argon atmosphere at a heating rate of 10 °C / min. After cooling to room temperature, the mixed solid obtained after calcination was dissolved with excess concentrated hydrochloric acid, then centrifuged and washed with deionized water three times. Finally, the sample was dried in a vacuum oven at 60 °C overnight to obtain a sample after molten metal zinc induced SMSI.
[0057] (3) In this example, the titanium dioxide-supported platinum nanoparticle catalyst obtained after SMSI was induced by molten metal tin was characterized by transmission electron microscopy (TEM), energy dispersive X-ray spectroscopy (EDS) and X-ray absorption spectroscopy (XAS).
[0058] like Figure 7 As shown, an amorphous coating layer obviously appeared on the surface of platinum nanoparticles supported by titanium dioxide, and the average size of the platinum nanoparticles was about 10 nm.
[0059] like Figure 8 As shown, signals of titanium, oxygen, and zinc appeared at the particles, among which the titanium and oxygen signals came from the outer coating layer.
[0060] Fig. 9 The EXAFS wavelet transform results show that the platinum nanoparticles have evolved into platinum-zinc-based intermetallic compounds, confirming that the molten metal strategy simultaneously achieves the construction of the coating layer and the alloying of the metal active phase, successfully expanding SMSI to the intermetallic compound system. Due to the presence of the coating layer, the active phase agglomeration and loss problems of intermetallic compound-based catalysts in harsh reaction environments will be effectively alleviated, and the stability of the catalyst will be significantly improved.
[0061] Comparative Example 2
[0062] It is basically the same as Control Example 1, except that the treatment temperature is increased to 700°C, and SMSI is constructed on the platinum nanoparticle catalyst supported on titanium dioxide using high-temperature hydrogen reduction. The Pt nanoparticles are not alloyed and evolved into intermetallic compounds, and the coating layer cannot exist stably in a high-temperature oxidizing atmosphere at 400°C.
[0063] Example 3
[0064] A method for constructing SMSI on a ceria-supported iridium nanoparticle catalyst induced by molten metal lithium, comprising the following steps:
[0065] (1) Preparation method of cerium dioxide supported iridium nanoparticle catalyst:
[0066] First, 40 mg of cerium dioxide was dispersed in 20 mL of deionized water and ultrasonically treated to make it uniformly dispersed. Then, 40 uL of 0.1 mol / L iridium chloride aqueous solution was gradually added under magnetic stirring, and then the solution was stirred dry in a 60°C water bath. After the obtained powder was fully ground, it was placed in a muffle furnace, heated to 300°C at a heating rate of 10°C / min, and calcined for 2 hours in a hydrogen-argon mixed gas with a hydrogen gas volume fraction of 10%. After cooling to room temperature, a cerium dioxide-supported iridium nanoparticle catalyst was obtained.
[0067] (2) Method of constructing SMSI by inducing molten metal lithium:
[0068] After 20 mg of cerium dioxide-supported iridium nanoparticle catalyst was fully covered with 1 g of lithium powder, it was calcined at 300 °C for 1 h in a tube furnace under argon atmosphere at a heating rate of 10 °C / min. After cooling to room temperature, the mixed solid obtained after calcination was dissolved with excess concentrated hydrochloric acid, then centrifuged and washed with deionized water three times. Finally, the sample was dried in a vacuum oven at 60 °C overnight to obtain a sample after molten metal lithium induced SMSI.
[0069] The coating layer constructed by molten metallic lithium still exists stably after being treated in a high-temperature pure oxygen atmosphere at 500°C for 1 hour, and no obvious agglomeration and growth of the catalyst is observed.
[0070] Example 4
[0071] A method for constructing SMSI on a gold cluster catalyst supported on zinc oxide induced by molten metal sodium, the specific steps are as follows:
[0072] (1) Preparation method of zinc oxide supported gold cluster catalyst:
[0073] First, 40 mg of zinc oxide was dispersed in 20 mL of deionized water and ultrasonically treated to make it uniformly dispersed. Then, 5 uL of 0.1 mol / L chloroauric acid aqueous solution was gradually added under magnetic stirring, and then the solution was stirred dry in a 60°C water bath. After the obtained powder was fully ground, it was placed in a muffle furnace and heated to 300°C at a heating rate of 10°C / min. It was calcined in a hydrogen-argon mixed gas with a hydrogen gas volume fraction of 10% for 2 hours. After cooling to room temperature, a zinc oxide-supported gold cluster catalyst was obtained.
[0074] (2) Method of constructing SMSI by inducing molten metal sodium:
[0075] After 20 mg of zinc oxide-supported gold cluster catalyst was fully covered with 1 g of sodium, it was calcined at 300 °C for 1 h in a tube furnace under argon atmosphere at a heating rate of 10 °C / min. After cooling to room temperature, the mixed solid obtained after calcination was dissolved with excess hydrochloric acid, then centrifuged and washed with deionized water three times. Finally, the sample was dried in a vacuum oven at 60 °C overnight to obtain a sample after SMSI was induced by molten metal sodium.
[0076] The coating layer constructed by molten metallic sodium still exists stably after being treated in a high temperature pure oxygen atmosphere at 500°C for 1 hour, and no obvious agglomeration and growth of the catalyst is observed.
[0077] Example 5
[0078] A method for constructing SMSI on a magnesium oxide-supported gold nanoparticle catalyst induced by molten potassium, comprising the following steps:
[0079] (1) Preparation method of magnesium oxide supported gold cluster nanoparticle catalyst:
[0080] First, 40 mg of magnesium oxide was dispersed in 20 mL of deionized water and ultrasonically treated to make it uniformly dispersed. Then, 40 uL of 0.1 mol / L chloroauric acid aqueous solution was gradually added under magnetic stirring, and then the solution was stirred dry in a 60°C water bath. After the obtained powder was fully ground, it was placed in a muffle furnace and heated to 300°C at a heating rate of 10°C / min. It was calcined in a hydrogen-argon mixed gas with a hydrogen gas volume fraction of 10% for 2 hours. After cooling to room temperature, a magnesium oxide-supported gold nanoparticle catalyst was obtained.
[0081] (2) Method of constructing SMSI by inducing molten potassium:
[0082] After 20 mg of magnesium oxide-supported gold nanoparticle catalyst was fully covered with 1 g of potassium, it was calcined at 400 °C for 1 h in a tube furnace under argon atmosphere at a heating rate of 10 °C / min. After cooling to room temperature, the mixed solid obtained after calcination was dissolved with excess hydrochloric acid, then centrifuged and washed with deionized water three times. Finally, the sample was dried in a vacuum oven at 60 °C overnight to obtain a sample after SMSI was induced by molten metal potassium.
[0083] The coating layer constructed by molten potassium metal still exists stably after being treated in a high-temperature pure oxygen atmosphere at 500°C for 1 hour, and no obvious agglomeration growth phenomenon is observed on the catalyst.
[0084] Example 6
[0085] A method for constructing SMSI on a ruthenium single atom catalyst supported on niobium pentoxide induced by molten metal Bi, the specific steps are as follows:
[0086] (1) Preparation method of ruthenium single atom catalyst supported by niobium pentoxide:
[0087] First, 40 mg of niobium pentoxide was dispersed in 20 mL of deionized water and ultrasonicated to make it uniformly dispersed. Then, 2 uL of 0.1 mol / L ruthenium chloride aqueous solution was gradually added under magnetic stirring, and then the solution was stirred dry in a 60°C water bath. After the obtained powder was fully ground, it was placed in a muffle furnace and heated to 300°C at a heating rate of 10°C / min. It was calcined for 2 hours in a hydrogen-argon mixed gas with a hydrogen volume fraction of 10%. After cooling to room temperature, a ruthenium single-atom catalyst supported by niobium pentoxide was obtained.
[0088] (2) Method of constructing SMSI by inducing molten metal bismuth:
[0089] After 20 mg of niobium pentoxide-supported ruthenium single-atom catalyst was fully covered with 1 g of bismuth powder, it was calcined at 400 °C for 1 h in a tube furnace under argon atmosphere at a heating rate of 10 °C / min. After cooling to room temperature, the mixed solid obtained after calcination was dissolved with excess hydrochloric acid, then centrifuged and washed with deionized water three times. Finally, the sample was dried in a vacuum oven at 60 °C overnight to obtain a sample after molten metal bismuth induced SMSI.
[0090] After the catalyst constructed with SMSI by molten metal bismuth was treated in a high temperature pure oxygen environment at 500℃ for 1 hour, no obvious agglomeration growth was observed.
[0091] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A supported metal catalyst after strong metal-carrier interaction induced by molten metal, characterized in that: Prepared by the following method: (1) Synthesizing supported metal catalysts by an impregnation method, which include oxide supports and metal nanoparticles, clusters or single atoms; (2) After the supported metal catalyst is fully covered with metal powder, the temperature is raised to above the melting point of the metal powder under the protection of an inert atmosphere to melt the metal powder, and the temperature is kept for 1-24 hours; after cooling to room temperature, the mixed solid is acid-washed with concentrated acid, centrifuged, and dried to obtain a supported metal catalyst after the molten metal induces the construction of a strong metal-support interaction; The oxide support is composed of a solid solution of one or more components selected from TiO2, V2O3, MnO2, Fe3O4, CeO2, Nb2O5, Ta2O5, MgO, Al2O3, SiO2, and ZnO; The metal nanoparticles are composed of one or more of Fe, Co, Ni, Ru, Rh, Pd, Os, Ir, Pt, Cu, Ag, and Au; The metal powder is one or more of Li, Na, K, Mg, Ca, Zn, Cd, Al, Ga, In, Sn, Pb, Sb, and Bi.
2. A method for preparing a supported metal catalyst after molten metal-support strong interaction is induced by the molten metal according to claim 1, characterized in that: The steps include: (1) Synthesizing supported metal catalysts by impregnation method, which include oxide supports and metal nanoparticles, clusters or single atoms; (2) After the supported metal catalyst is fully covered with metal powder, the temperature is raised above the melting point of the metal powder under the protection of an inert atmosphere to melt the metal powder, and the temperature is kept for 1-24 hours; after cooling to room temperature, the mixed solid is pickled with concentrated acid, centrifuged, and dried to obtain a supported metal catalyst after the molten metal induces the construction of a strong metal-carrier interaction.
3. The preparation method according to claim 2, characterized in that: The impregnation method comprises the following steps: dispersing the oxide carrier in water or ethanol, and ultrasonically treating it to make it uniformly dispersed; then, under magnetic stirring, dripping the metal precursor solution, heating the solution in a water bath to dry it; after fully grinding the obtained powder, heat-treating it in an atmosphere to obtain a supported metal catalyst.
4. The preparation method according to claim 2, characterized in that: The concentration of the metal precursor solution is 0.01-10 mol / L.
5. The preparation method according to claim 3, characterized in that: The water bath heating temperature is 40-90°C.
6. The preparation method according to claim 2, characterized in that: The mass percentage of metal nanoparticles, clusters or single atoms in the supported metal catalyst is 0.01-60wt%.
7. The preparation method according to claim 2, characterized in that: The oxide support is composed of a solid solution of one or more components of TiO2, V2O3, MnO2, Fe3O4, CeO2, Nb2O5, Ta2O5, MgO, Al2O3, SiO2, and ZnO.
8. The preparation method according to claim 2, characterized in that: The metal nanoparticles are composed of one or more of Fe, Co, Ni, Ru, Rh, Pd, Os, Ir, Pt, Cu, Ag, and Au.
9. The preparation method according to claim 2, characterized in that: The metal powder is one or more of Li, Na, K, Mg, Ca, Zn, Cd, Al, Ga, In, Sn, Pb, Sb, and Bi.
10. An application of a supported metal catalyst after molten metal induced construction of metal-support strong interaction as claimed in claim 1, characterized in that: The application is as a catalyst under oxidative environmental conditions.
Citation Information
Patent Citations
Method for preparing oxide-loaded metal, and application
CN113368851A
Manufacturing method for hybrid and alloy metal catalyst support using multi-melt-infiltration process of mixed metal salts and hybrid and alloy metal catalyst support thereof
KR1020130075980A